Nonlocal Dirichlet problem for linear parabolic equations with degeneration - Pukalskyi, I. D. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
In the spaces of classical functions with power weight, we prove the correct solvability of the Dirichlet problem for parabolic equations with nonlocal integral condition with respect to the time variable and an arbitrary power order of degeneration of coefficients with respect to the time and space variables.